PROFIL PROSES FERMENTASI RUSIP DENGAN PENAMBAHAN GULA AREN CAIR - Susilowati, Rukmini; Koesoemawardani, Dyah; Rizal, Samsul (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
This research was aimed to determine the microbiological and chemical characteristics of rusip with the addition of liquid palm sugar during fermentation.  Fermentation was carried out for 7 days and the observation was done after fermentation time of 0 hours (H1), 12 hours (H2), 24 hours (H3), 36 hours (H4), 2 days (H5), 3 days (H6), 4 days (H7), 5 days (H8), 6 days (H9) and 7 days (H10).  To obtain rusip fermentation profiles, the data were presented descriptively in tables and graphs.  Total lactic acid bacteria and lactic acid of rusip increased during fermentation, while pH, total fungi and total microbial decreased during fermentation. The chemical and microbiological characteristics of rusip on the seventh day of fermentation was : pH of 5.97, total lactic acid bacteria of 8.04 log CFU/g, total fungi  of 2.60 log CFU/g, total microbial of 9.87 log CFU/g, total lactic acid of 5.64% and total volatile nitrogen (TVN)  of 109.07 mg N/100 g. Keywords : liquid palm sugar, profil fermentation, rusip